Measuring the Level of Digital Financial Literacy Among Generation Y and Z in Indonesia - Aidil Fadli, Jul; Indradewa, Rhian; Yudistria, Yuyus (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
Digital financial literacy is a new concept that is an important part of financial literacy, especially in the context of Indonesia where the majority of the population is dominated by the younger generation. This study aims to measure the level of digital financial literacy in Generation Z in Indonesia, namely those aged between 17 and 26 years. The results showed that the majority of respondents had a good understanding of digital finance, including their awareness of financial risks, rights as consumers, and their understanding and experience in using various digital financial products. However, understanding of consumer rights and protection in digital financial services still varies. Most respondents felt uninformed about these aspects. On the other hand, adoption of digital payment solutions is very high, reflecting the convenience and widespread acceptance of the technology. However, knowledge about digital asset management products and fintech services related to financing and investment is still limited. These findings indicate that although digital financial literacy has developed, further educational efforts are needed to improve consumer understanding, especially regarding consumer protection and fintech services in financing and investment.